2014
DOI: 10.4236/pp.2014.511118
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Evaluation of Occidiofungin against Mice and Human Cancer Cell Lines

Abstract: Occidiofungin, a glyco-lipopeptide obtained from the liquid culture of Burkholderia contaminans MS14, has been identified as a novel fungicide. The natural product was shown to have a minimal amount of toxicity in a previous mouse toxicity study following intraperitoneal and subcutaneous administration. In this study, the toxicity of occidiofungin was evaluated following a 5 mg/kg intravenous tail vein injection. In addition, the toxicity of occidiofungin was evaluated against human fibroblast and cancer cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Occidiofungin was recently shown to have activity against human tissue culture cells in in vitro toxicity assays (Hing et al . ). Comparison of normal human primary cell lines with various human cancers demonstrated significantly higher toxicity values against the cancerous lines.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Occidiofungin was recently shown to have activity against human tissue culture cells in in vitro toxicity assays (Hing et al . ). Comparison of normal human primary cell lines with various human cancers demonstrated significantly higher toxicity values against the cancerous lines.…”
Section: Discussionmentioning
confidence: 97%
“…; Hing et al . ). Interestingly, in vitro toxicity studies have indicated that occidiofungin targets cancer cell lines with a T 50 value that is significantly higher than that found for Candida (Hing et al .…”
Section: Introductionmentioning
confidence: 97%
“…To date, the few actin binding antifungal compounds, including jasplakinolide (52, 53) and halichondramide (5456), are limited by their toxicity in animals at doses that would be required to demonstrate an efficacious effect. Occidiofungin, on the other hand, is well tolerated at 5 mg/kg or 20 mg/kg when administered intravenously or subcutaneously, respectively (22, 25). This dose is much higher than the MIC of occidiofungin against several fungal pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…This dose is much higher than the MIC of occidiofungin against several fungal pathogens. Furthermore, blood cells and blood chemistry following the administration of occidiofungin show no serious signs of toxicity (25). It is believed that the growth rates of the cells are attributed to the differences in killing activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation